South Africa Economic Update, August 2015 : Jobs and South Africa’s Changing Demographics - World Bank (Washington, DC, 2015)
Global growth hit a soft patch at the start of 2015. In the first quarter it slowed to 2.0 percent, quarter on quarter (q/q) annualized, from 2.3 percent in the fourth quarter of 2014. The slowdown was reflected in a decline in global manufacturing activity, on the back of weak industrial production and goods trade data, especially in large emerging markets. Among high-income countries, economic activity is strengthening. Euro Area growth picked up to 1.6 percent in the first quarter of 2015 from 1.3 percent the previous quarter. Growth in Japan accelerated to 2.4 percent in the first quarter from 1.1 percent in the previous quarter. For the second quarter, despite the uncertainty surrounding Greece, the Euro Area Composite PMI in July remained close to a four-year high. Confidence indicators for the second quarter point to further improvements, while indicators in Japan also suggest continued, albeit moderate, growth.